2006
DOI: 10.1002/cncr.22380
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell sarcoma of tendons and aponeuroses

Abstract: Specification factors regulate cell fate in part by interacting with transcriptional co‐regulators like CtBP to regulate gene expression. Here, we demonstrate that CtBP forms a complex or complexes with the Drosophila melanogaster Pax6 homolog Eyeless (Ey), and with Distal antenna (Dan), Distal antenna related (Danr), and Dachshund to promote eye and antennal specification. Phenotypic analysis together with molecular data indicate that CtBP interacts with Ey to prevent overproliferation of eye precursors. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
97
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 103 publications
(137 reference statements)
8
97
1
6
Order By: Relevance
“…Hierarchical clustering demonstrated leiomyosarcoma and MFH shared a similar protein expression profile, some of which was not distinguishable on the basis of protein expression, and that clear cell sarcoma, synovial sarcoma, and MPNST were grouped according to their protein expression patterns. These results were generally consistent with previous reports based on histologic and transcriptome analyses [7,13,19,25,[30][31][32].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hierarchical clustering demonstrated leiomyosarcoma and MFH shared a similar protein expression profile, some of which was not distinguishable on the basis of protein expression, and that clear cell sarcoma, synovial sarcoma, and MPNST were grouped according to their protein expression patterns. These results were generally consistent with previous reports based on histologic and transcriptome analyses [7,13,19,25,[30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…Clear cell sarcoma is also known as melanoma of soft parts and is derived from neural crest progenitor cells [19]. Nagayama et al [30] reported synovial sarcoma and MPNST shared similar expression patterns of numerous genes related to neural differentiation and suggested synovial sarcoma might be of neuroectodermal origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more than half of patients develop metastases and 5-year disease-specific survival is <50%. No targeted chemotherapies are available and conventional agents offer little benefit (2).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] İmmünohistokimyasal olarak HMB-45, S-100 ve Melan-A gibi melanoma özgül olanların yanı sıra, NSE, kromogranin gibi nöroendokrin belirleyicilerle de boyanma izlenebilir. [4][5][6][7]9,10 OLGU SUNUMLARI Kasım 2000-Haziran 2010 tarihleri arasında bö-lümümüzde tanı alan 4 adet TABHS olgusu değerlendirilmiştir. Olgularla ilgili yaş, cinsiyet lokalizasyonu, tümör çapı, tedavi şekli gibi klinik parametrelerin yanı sıra histopatolojik özellikler, histokimyasal ve immünohistokimyasal bulgular da araştırılmıştır.…”
unclassified